THE POLITICS OF A LOCAL SUFISM IN CONTEMPORARY INDONESIA: A Closed Look at The Shiddiqiyyah Tarekat - Ahmadi, Rizqa (UIN Sayyid Ali Rahmatullah Tulungagung, Indonesia, 2021)
This article discusses the politics of local Sufi group (tarekat) in Indonesia, the Shiddiqiyyah. It addresses the locality of Shiddiqiyah tarekat and its politics during New Order Indonesia and following the fall of the regime. It is argued that the Shiddiqiyah, a local tarekat with its roots in East Java and later successfully welcomes national reputation, is an example of a tarekat that utilizes nationalistic slogan to expand its influence as well as to protect the tarekat from heretic accusation. Through a series of intensive fieldwork, the article argues that the Shiddiqiyyah has successfully maintained ideological patronage to the New Order Indonesia through nationalistic slogan which has been a core value of the group. The doctrine of nationalism has been translated in Sufi and Javanese idioms and become fundamental doctrine of the Shiddiqiyyah.